Test and Development of Comprehensive Performance Test System for Shift Tower - Zhang Zhigang; Zheng Yanjie; Li Teng; Xu Dong; Hou Yabin; Yin Sheng (Jixie chuandong)
In order to study the comprehensive performance of shift tower in the manual transmission,a performance test system for the shift tower is designed. The test system adopts the selection and shift motor to drive the shift tower to realize the operating function of the gear selection and shift. According to the measurement and control requirements of the test system,the hardware and software of the measurement and control system are designed. Finally,taking the test system as the test platform,the performance test of the selection force-displacement characteristic and shift force-displacement characteristic of a certain shift mechanism are carried out. The test results show that the test system can really-time and accurately measure the performance parameters such as selection force,selection displacement,shift force and shift displacement,which provides experimental support for the research and development of the shift tower.